Meningkatkan Kemampuan Menyebutkan Anggota Tubuh Melalui Video Interaktif pada Anak dengan Gangguan Spektrum Autisme (GSA) (Single Subject Research A-B-A) - Tanzila, Lila; Tsaputra, Antoni; Iswari, Mega; Safaruddin, Safaruddin; Nasri, Yosa Yulia (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The results of observation and initial assessment at SLB Bunda Zikrillah Solok found a female first-grade student with Autism Spectrum Disorder (ASD) who had difficulty naming human body parts in the IPAS phase A of the Merdeka Curriculum. The learning media previously used, in the form of printed images, was considered less engaging and therefore had not been able to optimally improve the child's abilities. This study aims to test the effectiveness of using interactive video media in improving the ability to name body parts in children with ASD. This study uses a quantitative approach with a Single Subject Research (SSR) type and an A–B–A design. Data collection was carried out through direct observation of the target behavior in each session. The baseline phase A1 was conducted over three sessions until the data showed stability. The data were analyzed descriptively and visually by comparing trends, stability, and changes in ability levels across phases. The results of the study showed that in the first baseline phase (A1), the child's ability was at a stable score of 42.8. In the intervention phase (B), the ability gradually increased, reaching a score of 71.4. Furthermore, in the second baseline phase (A2), the child's ability increased further and stabilized at a score of 92.8. These findings indicate that interactive video media are effective in improving children’s ability to name body parts for children with low-class GSA and can be utilized as an applicable learning media alternative for teachers in Special Schools to enhance student engagement and understanding.